Supporting vegetable agrobiodiversity for better food and nutrition diversity: Insights from ethnic minority communities in Northern Vietnam - Phuong, Thi Nguyen; Swaans, Cornelis P.M.; Hoang, The Ky; Struik, Paul; Stomph, Tjeerd-Jan (International Institute of Knowledge Management, 2023)
10th International Conference on Agriculture 2023 (AGRICO 2023), in Bali, Indonesia, from 18-19 September 2023. Oral presentation titled “Supporting vegetable agrobiodiversity for better food and nutrition diversity: Insights from ethnic minority communities in Northern Vietnam”.